A general framework for scheduling equipment and manpower on container terminals - Sönke Hartmann (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2002)
In this paper, we propose a general model for various scheduling problems that occur in container terminal logistics. The scheduling model consists of the assignment of jobs to resources and the temporal arrangement of the jobs subject to precedence constraints and sequence-dependent setup times. We demonstrate how the model can be applied to solve several different real-world problems from container terminals in the port of Hamburg (Germany). We consider scheduling problems for straddle carriers, automated guided vehicles (AGVs), stacking cranes, and workers who handle reefer containers. Subsequently, we discuss a simple dispatching heuristic as well as a more advanced genetic algorithm for the general model. Based on a tailored generator for experimental data, we examine the performance of the heuristics in a computational study. We obtain promising results that suggest that the genetic algorithm is well suited for application in practice.
Keywords: 650; Container logistics; container terminal; optimization; scheduling; heuristics; genetic algorithm; Containerverkehr; Logistikdienstleister; Materialbedarf; Personalplanung; Scheduling-Verfahren; Theorie